2016
DOI: 10.1002/gps.4466
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the additional benefit of population screening for dementia beyond a passive case‐finding approach

Abstract: There is a very limited benefit of screening for dementia, as most people with dementia could be detected using a case-finding approach, and considerable potential for social and economic harm because of the low PPV associated with screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…A systematic review of trials to increase dementia diagnostic rates found no clearly successful single intervention [ 70 ]. However, a more proactive approach in primary care [ 71 ], in which patients or their families are asked about concerns regarding memory (when suspected) and how they potentially want to proceed, may pave the way for adjusted treatment and care.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of trials to increase dementia diagnostic rates found no clearly successful single intervention [ 70 ]. However, a more proactive approach in primary care [ 71 ], in which patients or their families are asked about concerns regarding memory (when suspected) and how they potentially want to proceed, may pave the way for adjusted treatment and care.…”
Section: Discussionmentioning
confidence: 99%
“…Although educating GPs increased their ability to diagnose dementia, this did not increase diagnostic rates in practice and local campaigns were ineffective on their own. A casefinding approach in primary care, where patients and families are asked about concerns about their memory and intent to act on them, may delineate a group who are more likely to have dementia (250). A recent intervention to increase timely diagnosis by empowering patients led to an increase in patients presenting to the GP but no change in the rate of referral to dementia diagnostic services (251).…”
Section: Timely Detection Of Dementiamentioning
confidence: 99%
“…A recent study suggested detecting dementia by case-finding based on subjective memory complaints [ 37 ]. However, we only found that 67.8% of dementia patients self-reported memory decline.…”
Section: Discussionmentioning
confidence: 99%